Creatine supplementation and sprint performance in soccer players - Mujika, I.; Padilla, S.; Ibanez, J.; Izquierdo, M.; Gorostiaga, E. (Medicine & Science in Sports & Exercise, 2000)
Purpose: This investigation examined the effects of creatine (Cr) supplementation on intermittent high-intensity exercise activities specific to competitive soccer. Methods: On two occasions 7 d apart, 17 highly trained male soccer players performed a counter-movement jump test (CMJT), a repeated sprint test (RST) consisting of six maximal 15-m runs with a 30-s recovery, an intermittent endurance test (IET) consisting of forty 15-s bouts of high-intensity running interspersed by 10-s bouts of low-intensity running, and a recovery CMJT consisting of three jumps. After the initial testing session, players were evenly and randomly included in a CREATINE (5 g of Cr, four times per day for 6 d) or a PLACEBO group (same dosage of maltodextrins) using a double-blind research design. Results: The CREATINE group's average 5-m and 15-m times during the RST were consistently faster after the intervention (0.95 ± 0.03 vs 0.97 ± 0.02 s, P < 0.05 and 2.29 ± 0.08 vs 2.32 ± 0.07 s, P = 0.07, respectively). Neither group showed significant changes in the CMJT or the IET. The CREATINE group's recovery CMJT performance relative to the resting CMJT remained unchanged postsupplementation, whereas it tended to decrease in the PLACEBO group. Conclusion: In conclusion, acute Cr supplementation favorably affected repeated sprint performance and limited the decay in jumping ability after the IET in highly trained soccer players. Intermittent endurance performance was not affected by Cr.